Pathogenic endoparasites of the spotted seatrout, Cynoscion nebulosus: patterns of infection in estuaries of South Carolina, USA - Arnott, Stephen A; Dyková, Iva; Roumillat, William A; de Buron, Isaure (Parasitology research, 2017)
Six types of pathogenic endoparasites in an economically important fish, spotted seatrout Cynoscion nebulosus, were studied in order to test whether prevalence of infection and assemblage richness varied with season, host sex, host size, or host age. Fish were collected from South Carolina estuaries, USA, over 12 months (n = 216; total lengths 15-663 mm). They were screened histologically for presence of Henneguya cynoscioni (Myxozoa) and Cardicola spp. (Digenea) in the heart, Kudoa inornata (Myxozoa) in the skeletal muscle, Sinuolinea dimorpha (Myxozoa) in the urinary system, Ichthyophonus sp. (Mesomycetozoea) in the kidney, and an unidentified microsporidian in the liver. Prevalence of infection was 29.8, 38.6, 47.2, 41.2, 13.6, and 2.8%, respectively. All factors had significant, but varying effects on the parasites. Parasite infections were more prevalent in winter than other seasons for Cardicola spp. and H. cynoscioni, more prevalent in winter and spring for Ichthyophonus sp., and more prevalent in male fish than female fish for K. inornata, S. dimorpha, and Ichthyophonus. Prevalence of infection by the three myxosporeans and Cardicola spp. increased with fish length, whereas prevalence of Ichthyophonus increased with length among young fish, but decreased with length among older fish. None of the factors affected the liver microsporidian, although statistical power was low due to its rareness. Assemblage richness varied between 0 and 5, was greater during winter and in male fish, and increased with fish length and fish age. Our results demonstrate that spotted seatrout are commonly co-infected by multiple pathogenic endoparasites, suggesting these parasites likely play an import role in controlling fish population numbers.
Keywords: Histology; Myxozoa; nemoci ryb; Estuaries; Fish Diseases; ryby; Parasitic Diseases, Animal; Female; Sciaenidae; Jižní Karolína; parazitární nemoci u zvířat; zvířata; Fishes; roční období; ženské pohlaví; Aporocotylidae; Male; Seasons; South Carolina; Animals; mužské pohlaví; estuár; Richness; Ichthyosporea